A lost decade: exploring F Scott Fitzgerald's contribution to the illness canon through the doctor–nurse series and other healthcare stories of the 1930s. Issue 2 (24th May 2012) - Kerr, Lisa
Abstract : F Scott Fitzgerald spent the 1930s writing about illness themes while he struggled with tuberculosis, insomnia, alcoholism, heart disease and the mental illness of his wife Zelda. During this decade, Fitzgerald published six stories that prominently feature hospitals and healthcare professionals. These stories, the 'doctor–nurse stories', along with nine additional published stories that touch upon medical themes have not previously been investigated as a thematic grouping. This paper explores the 1930s stories in the context of Fitzgerald's life and career in order to highlight his significant yet previously undervalued contribution to the canon of illness literature and his work's relevance to the field of literature and medicine.